Menu Planning for Diabetic Patients in Malaysia Using Integer Programming - Wan Shuhaimi, Wan Nur Aleeya Natasha; Md Sudin, Azila (Enhanced Knowledge in Sciences and Technology, 2026)
Diabetes management requires good dietary planning to meet nutritional needs while remaining affordable and practical. This study develops an Integer Programming (IP) approach to generate cost-minimized one-day meal plan for diabetic patients under three calorie levels: 1400 kcal for weight reduction in obese patients, 1600 kcal for weight maintenance for elderly patients, and 1800 kcal for weight gain for active individuals. A database of 32 food items categorized into three meals type: breakfast, lunch and dinner, where each item is relating to unit cost and nutrient composition values obtained from the Malaysian Food Composition Database (MyFCD). The proposed model minimizes total daily cost based on energy requirements and nutrient lower and upper bounds according to Recommended Nutrient Intake (RNI) Malaysia 2017. The optimization produced feasible menu plans for all three calorie levels, satisfying the specified nutritional constraints while minimizing total costs of RM15.00 for all calorie levels. The results demonstrate that IP can serve as a transparent support for decisions tool for designing nutritionally compliant and cost-effective menus for diabetic dietary planning across varying caloric needs.